PENINGKATAN AKTIVITAS PEMBELAJARAN MATEMATIKA MELALUI MODEL PEMBELAJARAN SFAE PADA KELAS IV SD INPRES BANGKALA III MAKASSAR - Jusmawati, Jusmawati; HS, Eka Fitriana (Universitas Pendidikan Mandalika (UNDIKMA), 2019)
Teachers and students activity are important things in learning process. This research aimed to know the improving of mathematics learning to the fourth grade students of SD Inpres Bangkala III Makassar by usingÂ SFAE learning model. Method of research was classroom action research in which this research applied mix method. This research was an assesment of some learning activity through four stages, namely planning, implementing, observing and reflecting. These stages were combine into each cycle. The subject of research was the fourth grade students of SD Inpres Bangkala III Makassar as 31 students including 12 male students and 19 female students. The observation of teachers and students was analyzedÂ by using descriptive quantitatve statistically. The result of research showed that teachers and students activity did not fulfill criteria in cycle I. Whereas cycle II showed that there was a good criteria classically.